Evolution of Takaful in Malaysia-the case of investment link family takaful - Parveen, Tamiza; Razali, Siti Salwani; Che Mohd Salleh, Marhanum (2020)
The Malaysian takaful industry has experienced stable growth in recent years. The industry has introduced an innovative product which is an investment-linked family takaful product that offers both investment and protection to the participants. These papers aims to explore the evolution of the takaful sector in Malaysia with a specific aim at unveiling the prospects and challenges with the investment-link products. This study is exploratory in nature. Thus, we have used a structured literature review techniques (SLR) to identify key papers in relation to Malaysian Takaful and investment link products. Review of related literature allows this paper to provide insight into the regulatory and shariah aspect of investment-linked takaful. We conclude that regulatory authorities need to develop governance and Sharia standards for the effective operation of Takaful operator toward protecting investor interest. Finally, we recommend the inclusion of the Shariah board to review investment options selected by the takaful operator.